Gender wage gap among couples and the role of parenthood across the wage distribution in Turkey - ÇAĞLAYAN AKAY, EBRU (My University, 2023)
The gender wage gap and the penalty of parenthood on wages are still major economic and sociological problems, especially in developing economies. This study aims to fill the void in the literature by analyzing the gender wage gap among couples and the role of parenthood across the unconditional wage distribution in the Turkish labor force. In accordance, 1198 families which include working-married-couples with and without children from the Turkish Household Budget Statistics survey data for 2018 are examined via unconditional quantile regression and decomposition methods. The findings provide insights into three problems of the labor force gender wage gap among couples, the role of parenthood on wages, and the variation of them across the wage distribution. The findings reveal a gender wage gap among couples and the gap is wider for the lower-paid employees. Lower-paid females face a wider motherhood wage penalty whereas fatherhood is mostly insignificant on the males\" wages. However, interestingly, fatherhood becomes a significant wage penalty for the highest-paid males.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Sosyal Psikoloji; İktisat; Social Sciences and Humanities; Psychology; Social Psychology; Economics; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Ekonomi ve İş; PSİKOLOJİ, SOSYAL; EKONOMİ; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; ECONOMICS & BUSINESS; PSYCHOLOGY, SOCIAL; ECONOMICS; Sosyal Bilimler ve Beşeri Bilimler; Ekonomi ve Ekonometri; Social Sciences & Humanities; Economics and Econometrics; Decomposition; Gender wage gap; Parenthood; Turkey; Unconditional quantile regression; Wage distribution